Allele-specific methylation of SSTR4 associated with aging and cognitive functions in patients with schizophrenia - Rongrong Zhao; Huihui Shi; Yanqiu Wang; Tao Jiang; Yahui Xu (PLoS ONE, 2025)
The co-occurrence of alcohol use disorder (AUD) and schizophrenia is prevalent, with a rate of 33.7%. Previous research has suggested a genetic and epigenetic overlap between these two disorders. SSTR4, a member of the somatostatin receptor family, is implicated in various neurological and psychiatric conditions, including cognitive function, AUD, and schizophrenia. However, the role of genetic-epigenetic interactions involving SSTR4 in patients with schizophrenia remains unexplored. In this study, we conducted an integration of publicly available datasets and identified allele-specific methylation patterns in SSTR4. Additionally, we pinpointed several genetic variants (rs17691954, rs11464356, rs3109190, and rs145879288) that influence the pace of aging and cognitive functions (rs705935) through their quantitative trait loci effects on CpG sites within SSTR4.